Techno-economic Feasibility of Bioethanol Production for Fossil Fuel-Fired Generating Plant in Nigeria - Anumaka , M.C.; Nwabueze, C. A.; Obi , P.I.; Offor , J. K., (African Journal of Education,Science and Technology (AJEST), 2014)
This paper examines the feasible and economic technology involved in production of bioethanol for fossil fuel-fired generating power plant in Nigeria. This work focuses on exploitation of recent development in the field of bioethanol production technology and devises feasible method for manufacturing bioethanol for both fuel-fired plants and blending bioethanol with oil-fuels for transportation in Nigeria. Implementation of this work will reduce environmental pollution and CO2 emission (which increases the global warming); and minimizes rapid depletion of fossil fuels as well as ensuring generation of clean, efficient, reliable, safe and affordable electricity in Nigeria